Proceedings of the 2019 CHI Conference on Human Factors in Computing Systems 2019
DOI: 10.1145/3290605.3300613
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to End-User Designers of Augmented Fabrication

Abstract: Augmented fabrication is the practice of designing and fabricating an artifact to work with existing objects. Although common both in the wild and as an area for research tools, little is known about how novices approach the task of designing under the constraints of interfacing with real-world objects. In this paper, we report the results of a study of fifteen novice end users in an augmented fabrication design task. We discuss obstacles encountered in four contexts: capturing information about physical objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…Prior work has shown that novice users may face multiple challenges while discovering or using public 3D designs on Thingiverse [2,16]. Since novice users tend to use online communities to fnd designs instead of learning 3D modeling, it is important that available design information and metadata should be organized in a clear and easy-to-understand manner to avoid potential confusions [5].…”
Section: Challenges and Techniques For Design Search And Retrievalmentioning
confidence: 99%
“…Prior work has shown that novice users may face multiple challenges while discovering or using public 3D designs on Thingiverse [2,16]. Since novice users tend to use online communities to fnd designs instead of learning 3D modeling, it is important that available design information and metadata should be organized in a clear and easy-to-understand manner to avoid potential confusions [5].…”
Section: Challenges and Techniques For Design Search And Retrievalmentioning
confidence: 99%
“…Creating mounts and fixtures for various objects is a general use-case made easier by easily accessible, low-effort Ephemeral Fabrication devices. Usually, when relying on CAD, the referential use of an object involves either scanning, measuring, or recreating the artifact in a different fashion [47]. This is not necessary when the object and the malleable material are allowed to interact.…”
Section: 23mentioning
confidence: 99%
“…There is a disconnect between the location of artifact design and the artifact's future location [4,37]. This requires either assessment and transfer of requirements, or methods to compensate measurement errors [27], which is a challenge that is not exclusive to novices.…”
Section: In-situ Tools For Personal Fabricationmentioning
confidence: 99%